The Effect of Work Life Balance and Job Crafting on Employee Work Engagement at Rejang Lebong Regional General Hospital - Sari, Qurnia Mitha; Nasution, Nasution (Jambura Economic Education Journal, 2025)
This study investigates the effect of work-life balance and job crafting on employee work engagement at Rejang Lebong Regional General Hospital. In the healthcare sector, where employees face high demands and stress, enhancing engagement is essential to maintain performance and service quality. This quantitative research involved 180 respondents selected through random sampling from a population of 620 employees. Data were gathered through a questionnaire that utilized a 5-point Likert scale and were examined using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The study aims to understand how personal life balance and proactive job adjustments impact employees’ engagement levels. The findings show that both work-life balance and job crafting have a significant and positive effect on work engagement, with an R² value of 0.758. These results highlight the importance of supporting employees in managing their work-life integration and encouraging job crafting to foster motivation, satisfaction, and productivity within healthcare institutions.